AB0446 Contraceptive Practices and Knowledge among Women with Systemic Lupus Erythematosus in A Portuguese Terciary Care Hospital. (15th July 2016) - Aguiar, F.; Fonseca, R.; Brito, I.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a disease that primarily affects women of reproductive ages. Unplanned pregnancy in women with SLE can have various complications both for the child and the woman, due to the disease itself or to eventual exposure to teratogenic medications. Most of these patients are candidates for extremely effective contraceptive methods, including implants, intrauterine devices (IUD) or permanent sterilization. However, some of these patients do not receive proper counseling and these methods are often underutilized. Objectives: To determine contraceptive use, knowledge and counseling among patients with SLE attending a portuguese terciary care hospital. Methods: Cross-sectional study in which women aged 15–50 followed in our Rheumatology Department with a diagnosis of SLE were approached to complete a researcher-administered survey. Results: 74 women were included, median age 34 years (range 15–50), with median disease duration of 9.0 years (range 0.50–30.0). 8 patients were in menopause, 2 were pregnant at the time of the survey, and 18 had not been sexually active with a man in the 3 months prior to the survey. 46 women (62.1%) were sexually active and were considered to be at risk for unintended pregnancy. 41.3% (n=19) of these patients were using extremely effective contraceptive methods with a typical use failure rate of ≤3% (10 of them using (IUD), 7 permanent sterilization, and 2 implants), 32.6% (n=15) were using highly effective contraceptive methods with a typical use failure rate of ≥3% but ≤10% (combined oral contraceptive in 7 and progestatin-only oral contraceptive in 8) and 26.1% (n=12) were using either no method, or low effective methods with a typical use failure rate of >10% (masculine condom in 11 and one patient was not using any method). 52.2% (n=24) of the sexually active women were taking one or more of methotrexate, mycophenolate mofetil, cyclophosphamide or warfarin. Amongst these soubgroup of patients one third was using extremely effective contraceptive methods, one third was using highly effective methods and another third was using low effective methods either or no method. Among women at risk for unintended pregnancy 13% (n=6) were not aware of the complications associated with pregnancy in their medical condition, and in patients using teratogenic medications 8.3% (n=2) were not aware of the the risks and 37.5% (n=9) had never been counseled about contraception. In women using teratogenic medications and low effective methods, 87.5% (n=7) were aware of the risks of pregnancy but 87.5% (n=7) had never been counseled about contraception. Conclusions: In this study, most women with SLE who are at risk for unintended pregnancy were aware that their medical condition increases the health risks for themselves and their fetuses. However a significant number of patients, especially those under potencially teratogenic medications did not receive any contraceptive counseling. It is essential to educate these women about their reproductive health and contraceptive options and risks. Disclosure of Interest: None declared